Analysis of Safety Culture Maturity on the Implementation of Occupational Safety and Health Management System in PT XYZ - Alfian Fakhri; Tranggono Tranggono; Rizqi Novita Sari (Universitas KH. Abdul Chalim Mojokerto, 2026)
PT XYZ is a company engaged in the energy sector in Indonesia. Based on the company's 2020-2023 report, minor work accidents occurred with the highest frequency and increased in 2021 and 2022. Moderate work accidents increased in 2023 and serious work accidents increased in 2021. The number of work accidents that occurred from 2020 to 2023 in the company remained relatively high. This indicates that OHS management is a crucial concern, so that it can reduce the number of work accidents. Therefore, this study aims to measure the level of maturity of occupational safety culture (OHS) so that it can be used as evaluation material or recommendations for OHS management in the company. This study will consider psychological, behavioral, and situational aspects and use seven dimensions: commitment, information & communication, leadership, organizational learning, competence, involvement & engagement, and responsibility, as well as a quantitative approach through the Analytic Hierarchy Process (AHP) method. The results of the study indicate that the level of maturity of XYZ's safety culture is 4.48, so the company is at the proactive safety culture maturity level. The proposed improvement recommendations are to ensure that the condition of PPE and work safety equipment is functioning properly, create SOPs for each position, hold regular briefings before each job is carried out, conduct work area inspections, install warning signs and safety information in the work area, document all work that has been done, conduct work safety training according to each worker's job description periodically, and hold regular meetings about the importance of K3.